The genomic basis for shell polymorphism in land snails - Johansen, Margrethe (2024)
The study of phenotypic variation in animals has been fundamental to biology since Darwin’s theory of evolution through natural selection, continuing through to the present day where the study of polymorphism continues to be an important factor in understanding genetics, evolution, and environmental adaptation. One group of animals that have a large degree of phenotypic variation are molluscs, evident in everything from the coiling direction of the shell to variations in colour and patterns. However, this phylum is often overlooked in genomic research with only a handful of available reference genome assemblies. In an effort to further understand the underlying genetic architecture of polymorphism, I explore in this thesis the genomic basis of polymorphism in land snails, with a focus on the classic study species of colour and banding patterns, Cepaea nemoralis, and the Japanese land snail Euhadra spp. I start by using whole-genome sequencing of a laboratory cross to construct a linkage map organising the highly fragmented C. nemoralis reference genome into a high-density linkage map. I then use this to map the location of two shell phenotypes in Cepaea, the colour locus, which forms part of the Cepaea supergene, and the unlinked mid-banded locus. Following on from this, I validate the positions of these two loci through genome-wide association analyses using the same laboratory cross and an independent dataset of wild C. nemoralis. These analyses further refine the position of the colour locus to a single contig, and through a combination of gene prediction and annotation I identify a triplication of a polyketide synthase (PKS) gene as the most likely candidate for the colour locus. Finally, I focus on the chiral variation in the Japanese snail Euhadra, and as a first step in unravelling the genomic basis of left-right body asymmetry I attempt to assemble a draft reference genome of E. quaesita. Enlightened by the characteristics of molluscan genomic architecture I explore the unsuccessful assemblies and identify how future projects might succeed.